LAZNAS STRATEGY OF THE BALI DAKWAH COUNCIL IN INCREASING THE PHILANTHROPY INTEREST OF THE DENPASAR CITY COMMUNITY - Roisatul Amanah, Riza; Riduwan, Riduwan (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2025)
This research aims to find out the strategy of the LAZNAS Bali Da'wah Council in managing Zakat, Infaq, and Alms, to find out the increase in public philanthropic interest in giving Zakat, Infaq, and Alms, and to find out how the sharia economic analysis of the Bali Da'wah Council, LAZNAS, in managing Zakat, Infaq, and Alms. The research method uses a qualitative descriptive approach with direct interviews in the field. The instrument analysis approach uses strategic management approach instruments, philanthropy theory, and Sharia management. This research shows that the LAZNAS Da'wah Council's strategy in managing zakat, infaq, and alms consists of planning, promotion, collection, distribution, and evaluation strategies. The LAZNAS Da'wah Council in managing zakat, infaq, and alms is implemented based on Sharia management. It contains strategies for sharia economic principles as taught by the Prophet Muhammad, which include justice, trustworthiness, accountability, communicativeness, the qualities of honesty (sidq), and having intelligence (fathanah ).